KEPEMIMPINAN STRATEGIS DALAM PERSPEKTIF GENDER - Hasto Kristiyanto; Purnomo Yusgiantoro; Amrulla Octavian; I Wayan Midhio (JISOS: JURNAL ILMU SOSIAL, 2022)
Discrimination and injustice against women still occur in various aspects of life. Gender inequality is caused by social culture as the influence of patriarchal understanding that places domination on men. In the midst of these various forms of gender inequality, positive law has provided a constitutional footing for women. This can be seen in the democratic system in Indonesia which gives equal rights to every citizen to vote and be elected. The issue of women's leadership in national defense requires a comprehensive multidisciplinary study. The approach from the aspects of women's systems, policies, procedures, and affirmative policies in the national defense system requires a special study. Various obstacles arise related to physical problems, endurance, totality, and various demands for quality standards for human resources. Indonesian women's leadership has historically gained legitimacy, and throughout the history of Indonesian civilization, there have always been women leaders who answered the call of Indonesian history. A cultural strategy is needed as the basis for the women's emancipation movement to overcome various cultural barriers, religious dogma, social inequality, and educational disparities through educational programs. female character. The cultural strategy is carried out through a process of political education and the regeneration of women's leadership as pioneers. Thus, women's leadership apart from adopting the concept of strategic thinking is also rooted in the nation's culture. Both can go hand in hand. Political education and the regeneration of women's leadership must be carried out in stages, massively, and systematically in order to overcome various gender disparities.